2020
DOI: 10.32819/020008
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Winter Wheat Plant Structure Mutations by Chemomutagenesis

Abstract: The objectives of our investigations are to describe the variation by muta-tions of stem architecture of the modern Ukrainian winter wheat varieties accord-ing to their interactions with mutagen nature, concentration and genotype-mutagen interaction specific. 7 modern Ukrainian winter wheat varieties and one line were treated by 1.4-bisdiazoatsetilbutan water solution at 0.1 and 0.2% concentrations. Types of visible mutations like as high and short stem, dwarfs and semi-dwarfs, changes in a waxy bloom, stem th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…На сьогодні метод експериментального мутагенезу застосовують з різними селекційними цілями: одержання макро-і мікромутацій якісних та кількісних ознак для добору чи прямого практичного використання, подолання несхрещуваності віддалених форм, вплив на кросинговер у гібридів, пригнічення реакції самоне-сумісності в рослин-перехресників, індукування поліплоїдії тощо [15]. У мутагенезі виникають можливості змін напряму та характеру генетично зумовлених кореляційних зв'язків, зокрема і при перенесенні мутантного гена до нового генетичного середовища [16]. Сучасні дослідження спрямовані на підвищення ефективності індукування різноманітних оригінальних і селекційно-цінних мутантів, а також створення принципових джерел рослин з високими продуктивністю, урожайністю, якістю зерна та стійкістю до біотичних й абіотичних чинників навколишнього середовища [17].…”
Section: фізіологія рослин і генетика 2022 т 54 №unclassified
“…На сьогодні метод експериментального мутагенезу застосовують з різними селекційними цілями: одержання макро-і мікромутацій якісних та кількісних ознак для добору чи прямого практичного використання, подолання несхрещуваності віддалених форм, вплив на кросинговер у гібридів, пригнічення реакції самоне-сумісності в рослин-перехресників, індукування поліплоїдії тощо [15]. У мутагенезі виникають можливості змін напряму та характеру генетично зумовлених кореляційних зв'язків, зокрема і при перенесенні мутантного гена до нового генетичного середовища [16]. Сучасні дослідження спрямовані на підвищення ефективності індукування різноманітних оригінальних і селекційно-цінних мутантів, а також створення принципових джерел рослин з високими продуктивністю, урожайністю, якістю зерна та стійкістю до біотичних й абіотичних чинників навколишнього середовища [17].…”
Section: фізіологія рослин і генетика 2022 т 54 №unclassified
“…Wheat, which occupies more than 200 million hectares in the world, is considered as one of staple grain crops (Rauf et al, 2015;Bondarenko & Nazarenko, 2020;Nazarenko, 2020). Within the period 2016-2020, on average 753-763 million tons of wheat grain was produced annually in the world (Food Outlook -Biannual Report on Global Food Markets.…”
Section: Introductionmentioning
confidence: 99%
“…But even earlier, studies of other objects have shown that other types of changes (in particular, paracentric inversions) are quite often more likely causes of hereditary changes than much rarer translocations (Palmieri et al, 2016), although this type of change is more promising for cultivated plants. Already at the early stages of research, it became clear that chromosomal aberrations play an essential role in the evolution of living organisms (Oney-Birol & Balkan, 2019;Nazarenko, 2020). The study of plant chromosomes in pachytene (Küçük & Liman, 2018) made it possible to establish that such types of rearrangements as dele-tions, duplications, inversions and translocations have a complex and complex character (Spencer-Lopes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As for the instability of the genome, there is a phenomenon that is directly related to the nature of the genotype of a particular individual, obviously with the presence of highly variable loci. The mechanism of the phenomenon is not entirely clear, since it is not explained by any of the basic principles of radiobiology and genotoxicology, such as dependence on the dose (concentration), the nature of the mutagen, or the interaction of the mutagen and genotype (Nazarenko, 2018(Nazarenko, , 2020Yali & Mitiku, 2022).…”
Section: Introductionmentioning
confidence: 99%